Identification of the U-box gene family in peach (Prunus persica) and functional analysis of PpPUB20 in response to salt stress - Zhang, Huiwen; Guo, Ruxuan; Zhang, Xiaoshuang; Zhao, Chongyu; Wu, Junkai; Xiao, Xiao; Shen, Yanhong; Liu, Chunsheng; Li, Gang; Su, Kai; Xiao, Kun; Zhang, Chenguang; et al. (Frontiers in Genetics, 2025)
BackgroundWith the rising proportion of saline soils in the global irrigated soil area, improving salt stress tolerance in peach is of great significance and value for the development of peach industry. Plant U-box proteins (PUBs) are widely involved in various stress response processes. In this study, genome-wide identification and analysis of PUBs genes in cultivated peach were carried out, and the expression profiles of peach PUB genes in different tissues of peach as well as their responses under salt stress were also investigated.MethodsThe genome-wide identification of PUBs genes in cultivated peach was analysed by gene localisation, gene structure and evolutionary analysis. Subsequently, the expression profiles of PpPUB genes in different tissues of peach and the changes in the relative expression of peach PUB genes under ABA, GA3, IAA, 6-BA treatments, low-temperature stress and salt stress were investigated.Results and discussionIn this study, 51 U-box protein genes (PUB) were identified in the cultivated peach “SJZX” and divided into six groups. Most of the PpPUB were predicted to be located in the nucleus and chloroplasts. Promoter analyses indicated that most members may be associated with lightresponsive processes. Expression analysis based on RT-qPCR showed that most PUB members in peach were highly expressed in a certain tissues or organs. Based on the results of RT-qPCR expression analysis of 18 representative PpPUB after abiotic stress and hormone induction, all detected genes except for PpPUB19 were induced by salt stress, and PpPUB3/20/23/49 were induced by low temperature. Multiple genes were induced or repressed by exogenous hormone treatments. Furthermore, Arabidopsis seedlings heterologously overexpressing PpPUB20 exhibited greater salt tolerance than wild-type seedlings under the same salt stress conditions. These findings provide comprehensive information on the PpPUB family and identify PpPUB members that may be involved in the regulation of hormones and salt stress. Therefore, this study enhances the understanding of potential role of PpPUB in stress adaptation in peach, thereby establishing a foundation for subsequent functional investigations and applications in stress-resistant crop breeding.